Social media and project management: Symbolism in action - Delerue, H.; Cronje, Tom (Cambridge University Press, 2017)
© Cambridge University Press 2017. Introduction This chapter examines some reasons why project teams would use social media. Social media were just beginning to be co-opted by business interests in the 2010s (Kiron, Palmer, Phillips, & Kruschwitz, 2012): early adopting firms – the ones that tend to adopt social media applications – can be viewed as innovators, driven by efficiency and profit gains (e.g., Delerue & Cronje, 2015; Perrigot, Kacker, Basset, & Cliquet, 2012). Social media generally provide: Web-based platforms that allow workers to (1) communicate messages with specific coworkers or broadcast messages to everyone in the organization, (2) articulate a list of coworkers with whom they share a connection, (3) post, edit, and sort text and files linked to themselves or others, and (4) view the messages, connections, text, and files communicated, articulated, posted, edited and sorted by anyone else in the organization at any time of their choosing. (Leonardi, Huysman, & Steinfield, 2013, p. 2) The development of complex products, services, and processes with very short time-to-market combined with needs for cross-functional expertise have compelled increasing numbers of organizations to implement their business operations as projects (Kerzner, 2002). Projects have been described as temporary organizations that are strongly focused on a defined task, and therefore very agile. In addition, projects are ephemeral in the sense that the knowledge that is gained through the project quickly evaporates after the project team is disbanded (Gemünden, 2013, p. 2). An essential component of project execution is the information that feeds decision making and knowledge creation. Some researchers therefore view social media – which are used to convey information – as valuable for project management (Harrin, 2010; Remidez & Jones, 2012; Rimkuniene & Zinkeviciute, 2014). For instance, Rimkuniene and Zinkeviciute (2014) demonstrate how social media can enhance effective communication in temporary organizations by addressing specific project-based needs. Remidez and Jones (2012) emphasize that project managers must understand the relationships between communication practices and trust development, and how they are affected by social media. According to Harrin's (2010) study on social media in project environments, over two-thirds of 181 project managers surveyed across thirty-two countries believed that social media constitute a key issue for their industry (Harrin, 2010).